Prevalence of intestinal parasitic infection among school children in Kirtipur Municipality, Kathmandu - Dahal, Amulya; Roka, Dev Bahadur; Prasad, Shiv Mangal; Shrestha, Srishti (Nepal Medical College Journal, 2022)
Intestinal parasitic infections are a major cause of morbidity in developing countries including Nepal. Most common intestinal parasites reported in Nepal are Ascaris lumbricoides, Hymenolepis nana, Hookworm, Trichuris trichiura, Giardia lamblia and Entamoeba histolytica. This study aimed to find out the prevalence of various intestinal parasitic infections among school children in Kirtipur Municipality, Kathmandu. A cross-sectional observational study was carried out with prepared questionnaire and stool examination between October to November, 2021. Altogether, 409 stool samples were randomly collected from different schools and examined by direct smear method. Out of 409 stool samples, 73 (17.8%) were positive and 336 (82.1%) were negative. Among positive cases, helminthic infection was seen in 45 (11.0%) and protozoan infection was found in 28 (6.8%). Altogether eight species of intestinal parasites were detected, the most common was A. lumbricoides (34.2%), followed by protozoa G. lamblia (23.3%), E. histolytica (15.1%), T. trichiura (10.96%), Hookworm (6.8%), Enterobius vermicularis (4.11%), Taenia solium (4.11%) and H. nana (1.37%) respectively. Study showed that, there was 63 (86.30%) single infections, 9 (12.33%) double infections and 1 (1.37%) multiple infection. The present study reveals that intestinal parasites are abundant among students of Kirtipur Municipality, Kathmandu. The situation strongly calls for the use of control measures including treatment of infected individuals, improvement of health status of infected students by health education, public health awareness and also develop the health care facilities and aware the people for the utilization of health services.